Career Counselling First Nations Youth: Applying the First Nations Career-Life Planning Model - Neumann, Harly; McCormick, Rod M.; Amundson, Norman E.; McLean, Holly B. (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of the study was to field-test the First Nations Career-Life Planning Model, developed by McCormick and Amundson (1997), to determine, from participant feedback, if the model was viable, practical, and culturally appropriate. First Nations youth as well as family and community members participated in career counselling sessions and provided feedback on the model. The comments and feedback were categorised into five themes that support and suggest ways of improving the model further. Implications for practice and future research are included.